considere a função
![f(x) = {4}^{x} f(x) = {4}^{x}](https://tex.z-dn.net/?f=f%28x%29+%3D++%7B4%7D%5E%7Bx%7D+)
calcule:
![f( - 3) f( - 3)](https://tex.z-dn.net/?f=f%28+-+3%29)
![f( \frac{1}{2} ) f( \frac{1}{2} )](https://tex.z-dn.net/?f=f%28+%5Cfrac%7B1%7D%7B2%7D+%29)
Soluções para a tarefa
Respondido por
1
Resposta:
f(x) = 4^x
f(-3) = 4^-3
f(-3) = (1/4)^3
f(-3) = 1/64
f(1/2) = 4^1/2
f(1/2) = √4
f(1/2) = 2
Explicação passo-a-passo:
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás